A Framework for Planning Stress Control Interventions - Hiebert, Bryan A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper is of potential use to counsellors planning stress-related interventions with clients. Initially a conceptual framework is presented. The differences between demands, pressures, stressors and stress; the role of personal coping in the stressful experience; and the differential effects of transitory and chronic stress are discussed. Next, an overview of data-based stress control procedures is presented. Stresso rmanagement strategies, focusing on changing the situation to reduce the pressure, are treated separately from stress management strategies, focusing on changing the person's reaction to the situation. These strategies are divided further into twogroups, "use-as-required" or "use continuously", based on the amount of life-style change and client commitment required. Finally, an assessment procedure is outlined that can be used in both a diagnostic and a prescriptive way to plan stress intervention.